2012
DOI: 10.1177/0272431612450950
|View full text |Cite
|
Sign up to set email alerts
|

Important Nonparental Adults as an Academic Resource for Youth

Abstract: This study examined the associations between various sources of social support and academic achievement. Participants were 313 ethnically diverse students attending a low-income intermediate school in New Zealand (mean age = 11.96 years). They reported on the presence and nature of a relationship with a very important nonparental adult in their lives (VIP), and on parent, peer, and VIP warmth and acceptance. Indicators of academic achievement (standardized tests) were also gathered from the school. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…Interestingly, social support was not directly associated with participants' GPA or grades. This finding was not in line with previous research which found a link between social support and classroom grades for adolescents living in poverty [8,22]. It may take more time for the support provided by the current CAP to directly impact GPA or grades.…”
Section: Social Support and Adolescent Outcomescontrasting
confidence: 96%
See 2 more Smart Citations
“…Interestingly, social support was not directly associated with participants' GPA or grades. This finding was not in line with previous research which found a link between social support and classroom grades for adolescents living in poverty [8,22]. It may take more time for the support provided by the current CAP to directly impact GPA or grades.…”
Section: Social Support and Adolescent Outcomescontrasting
confidence: 96%
“…In general, studies have linked social support to a number of adolescent outcomes including academic outcomes [9], internalizing problems, and depression [7,21]. Among adolescents that have been exposed to risk, social support has been also found to improve outcomes [22]. For instance, [22] found that social support from adults was related to higher academic achievement for adolescents from lower income families.…”
Section: Social Support and Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…"Very important nonparental adults" have strong mentoring influences on youths' ability to access higher education (Beam et al 2002). Nonparental adult mentor relationships are also correlated with higher academic scores and healthier social ties with family, friends, and classmates (Beam et al 2002;DuBois and Silverthorn 2005;Farruggia et al 2013). Adult mentors are able to combine fun and maturity, supporting the mentees autonomy and independence while role modeling (Allen and Land 1999;Beam et al 2002;Rhodes 2002;Rhodes 2005).…”
Section: Mentoring and Educationmentioning
confidence: 99%